Sooraj Mukhi class 7 Urdu ka Guldasta - Fozia Ehsaan Farooqi; Fozia Ehsaan Farooqi (Lahore Oxford, 2024)
It is a very nice textbook with multiple stories and poems. it has stories about many pakistani heroes, fights, and victories. It teaches alot of things ...
Keywords: Text book